PENGELOLAAN PRASARANA PARIWISATA PADA DESTINASI PANTAI KETAM DI DESA PONGKAR KABUPATEN KARIMUN KEPULAUAN RIAU - Kurniawati, R. Irpika; Sidiq, Rd. Siti Sofro Sidiq (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2026)
Tourism infrastructure management is a crucial aspect of supporting the sustainability and quality of a tourist destination. This study aims to describe and analyze the management of infrastructure at Pantai Ketam, Pongkar Village, Karimun Regency. The research focuses on management mechanisms viewed from four management functions: planning, organizing, actuating, and controlling, across the dimensions of accessibility, utilities, and service networks. The study employs a descriptive qualitative method with data collection techniques including observation, in-depth interviews, and documentation. The results indicate that infrastructure management at Pantai Ketam is still informal and family-based. In the planning and organizing stages, development strategies are carried out gradually and orally without a formal structure. The implementation stage shows optimal results in the aspects of main road access and service networks (gazebos and art stages), but still faces constraints in water utility capacity and internal parking arrangement. Meanwhile, monitoring is conducted manually by the manager and through periodic reviews by the Village Government. Based on these findings, it is necessary to increase utility infrastructure capacity and formalize governance to ensure tourist comfort and destination sustainability. Keywords: Management, Tourism Infrastructure, Pantai Ketam, Marine Tourism, Pongkar Villag